Microeconomic theory - Ferguson, C. E.; Gould, John P. (Homewood, Ill. : R. D. Irwin, 1975)
This fourth edition of Microeconomic Theory, like the three earlier editions, is a textbook on neoclassical price theory intended primarily for undergraduate students. A major addition in this edition is a new chapter (Chapter 10) on analytical uses of models of competition and monopoly, which replaces the chapter on Linear Programming. This new chapter is intended to illustrate how the theoretical tools of economics can be used to analyze the effects of such things as taxes, subsidies, and price controls on firm and industry price and output. Students will find this material very useful.
Includes bibliographical references and index.
rpm 07/07/2017
Loans
Keywords: Microeconomics